Model-based integration of ecology and socio-economics for the management of biodiversity and ecosystem services: State of the art, diversity and current trends. (December 2020) - Drechsler, Martin
Abstract: Models are important tools to integrate ecological and socio-economic knowledge to better understand and manage social-ecological systems. Challenges include, among others, the adequate representation of feedback loops between the socio-economic and the ecological subsystems, uncertainties and human behaviour. To analyse how well models are able to address these challenges in the fields of biodiversity conservation and ecosystem services management the present paper systematically reviews recent mechanistic models of the field and analyses them with respect to a number of binary criteria. The reviewed models generally contain quite a few of the above-mentioned system features but still fall short when it comes to the adequate representation of the socio-economic dimension. Sorting the models by the labels given to them by their authors, such as "ecological-economic" or "system-dynamic", allows assessing model variation within and among labels and indicates that there is a fruitful level of diversity in the models. Highlights: Papers with models integrating ecological and socio-economic knowledge are reviewed. Considered fields of application are biodiversity conservation and ecosystem services. Models contain important features but generally miss important socio-economic issues. There seems to be a fruitful level of diversity among the models in the field.